SISTEM INFORMASI BIMBINGAN KONSELING PADA SMA NEGERI 6 TANJUNG JABUNG TIMUR BERBASIS WEB: Guidance Counseling, MySQL, PHP, Information Systems, Web. - -, Mulyadi (JURNAL AKADEMIKA, 2018)
The rationale for the implementation of guidance and counseling in schools is not merely the location of the existence or absence of a legal basis or provisions from above, but more important is the effort to facilitate students, hereinafter referred to as counselors, to be able to develop their potential or achieve tasks - task of development (concerning physical, emotional, intellectual, social, and moral-spiritual aspects). Preparation of prospective students at Tanjung Jabung Timur Public High School 6 to continue higher education in order to produce graduates who are qualified and able to enter the workforce does not only pay attention to the subject matter but the process of forming student personality also needs to be considered. Analysis and design modeling uses the PHP programming language and MySQL database server. Guidance and Counseling (Guidance of Counseling) in schools plays an important role in the process of forming students' personal. What role can it be effective if counseling in schools is supported by a structural mechanism in a school. The purpose of this system is to help the Counseling Guidance teachers at Tanjung Jabung Timur sma negeri 6 to provide services to students so as to produce quick and objective decisions in the counseling process. The results of this Final Project are to determine the development of student personality which can be used by the teacher in determining the increase in class and coaching for students.